P Profil Kromatografi Dan Penetapan Kadar Flavonoid Total Fraksi Etil Asetat Daun Kalangkala (Litsea Angulata Blum) Menggunakan Spektrofotometri Uv-Vis: Profil Kromatografi Dan Penetapan Kadar Flavonoid Total Fraksi Etil Asetat Daun Kalangkala (Litsea Angulata Blum) Menggunakan Spektrofotometri Uv-Vis - Mardlatillah, Mardlatillah; Rohama, Rohama; Kurniawati, Darini (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: Kalangkala is a fruit plant typical of Kalimantan and belongs to the species of the genus Litsea which is thought to have potential as a natural antioxidant. Empirically, some people in South Kalimantan use the kalangkala plant, especially the seeds of the fruit, to treat boils. One of the compounds that have antioxidant and antibacterial content is flavonoids.Objectives: To determine the thin layer chromatography profile of the total flavonoid compound of the ethyl acetate fraction and to calculate the total flavonoid content of the ethyl acetate fraction of the leaf extract of Kalangkala (Litsea angulata Blum).Method: Thin Layer Chromatography Profile and Determination of Total Flavonoid Content of the Ethyl Acetate Fraction of Kalangkala Leaf Extract using the UV-Vis Spectrophotometry method. The data were then analyzed qualitatively and quantitatively.Results: The chromatographic profile of the total flavonoids of the ethyl acetate fraction of Kalangkala leaf eluent that was most optimal was Ethyl acetate : n-Hexane (3:7) because it showed the most stains, namely 5 stains. And in the uv-vis spectrophotometry method, the total flavonoid content of the ethyl acetate fraction of Kalangkala leaves (Litsea angulata Blum) was 0.9 mg QE/g.Conclusion: Kalangkala leaf extract on the TLC profile using ethyl acetate : n-Hexane (3:7) showed a total of 5 stains. And the value of the total flavonoid content of the ethyl acetate fraction of kalangkala leaves was 0.9 mg QE/g.